Karakterisasi Penalaran Proporsional Siswa dalam Memecahkan Masalah Rasio dan Proporsi Berdasarkan Kemampuan Dasar Matematika - Rahaded, Sara; Tuasikal, Abdullah (COGNITIVISM: Journal of Educational Research and Development, 2025)
This study aims to determine the characterization of students' proportional reasoning in solving ratio and proportion problems based on the basic mathematics ability of grade VII of Al-Wathan Ambon Junior High School. The type of research used is qualitative descriptive. The number of subjects in this study amounted to 1 person who was selected using the purposive sampling technique. The instruments used are tests and interviews. The data analysis technique used is qualitative descriptive, which consists of data reduction, data presentation, and conclusion drawing. The results of data analysis were obtained that subjects in the learning process and in solving problems in social arithmetic material were able to reflect the characteristics of proportional reasoning and meet 3 of the 4 indicators of proportional reasoning ability used in this study, namely having a covariated understanding, recognizing proportional relationships that are different from non-proportional relationships in the real-world context, and developing many strategies to solve proportions or comparing ratios. This is based on the results of interviews conducted directly on the subject, namely in solving the problem, the subject is able to have a varied understanding of the given problem, is able to understand the relationship patterns contained in the problem to help him solve the problem, and is able to develop a problem-solving strategy.